Possible Antineoplastic Agents, Part XVII: Synthesis, Antitumor and Antiangiogenic Study of Few Bioisosteres of Thalidomide Metabolites - Sen, S.; Sarker, K.; Ghosh, A.; Mishra, S.; Saha, A.; Goswami, D.; Gupta, J.K.; De, A.U. (Asian Journal of Chemistry, 2011)
Two series of bioisostere of thalidomide metabolites and their cyclized variants were designed, synthesized and characterized. In vivo antitumor activity was studied on EAC in swiss albino mice. Cytotoxicity study was carried out on HUVEC and Vero cell lines by MTT assay method. Antiangiogenic activity on Ehrlich ascites tumor (EAT) was investigated studying inhibition of formation of micro vessels by identification of CD31 antigen through immunohistochemistry. One molecule has exhibited both antitumor and antiangiogenic activity but there is no significant toxic effect on normal cell.